The role of CD8+ t cells in endometriosis: a systematic review - Kisovar, A; Becker, C; Granne, I; Southcombe, J (Frontiers Media, 2023)
Background: Endometriosis is a chronic disease affecting 6–10% of women of reproductive age. It is an important cause of infertility and chronic pelvic pain with poorly understood aetiology. CD8+ T (CD8 T) cells were shown to be linked to infertility and chronic pain and play a significant role in lesion clearance in other pathologies, yet their function in endometriosis is unknown. We systematically evaluated the literature on the CD8 T in peripheral blood and endometriosis-associated tissues to determine the current understanding of their pathophysiological and clinical relevance in the disease and associated conditions (e.g. infertility and pelvic pain).